2015
DOI: 10.1039/c5cc05732a
|View full text |Cite
|
Sign up to set email alerts
|

How does relativity affect magnetically induced currents?

Abstract: Magnetically induced probability currents in molecules are studied in relativistic theory. Spin-orbit coupling (SOC) enhances the curvature and gives rise to a previously unobserved current cusp in AuH or small bulge-like distortions in HgH2 at the proton positions. The origin of this curvature is magnetically induced spin-density arising from SOC in the relativistic description.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“… at four‐component relativistic level, which had allowed the extraction of the SO contributions to these current loops. Current plots showed diatropic current loops (see also ref. ) around the hydride in HAu and small SO‐induced localized paratropic current loops for HHgH, consistent with shielding 1 H σ SO for HAu and a deshielding one for HHgH (cf.…”
Section: Resultsmentioning
confidence: 99%
“… at four‐component relativistic level, which had allowed the extraction of the SO contributions to these current loops. Current plots showed diatropic current loops (see also ref. ) around the hydride in HAu and small SO‐induced localized paratropic current loops for HHgH, consistent with shielding 1 H σ SO for HAu and a deshielding one for HHgH (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, relativistic effects on interatomic currents have been reported for the molecules AuH and HgH 2 . [20] In general, only a few authors have investigated interatomic currents; the studies of hydrogen bonded systems via MICDs appear as the most relevant ones. [21,22] The literature on other attempts to extract chemical information from MICDs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the influence of the SO coupling on MICDs is only significant for the Bi5 and Mc5 clusters. Other authors have also reported important changes, on magnetic properties, upon inclusion of the SO coupling in their calculations …”
Section: Resultsmentioning
confidence: 89%
“…The SO coupling has been reported to affect magnetic and aromatic properties on molecules containing heavy atoms . For example, in the MICD study of the hexahalogenated benzenes normalC6normalX6 ( X=H,F,Cl,Br,I,At), the SO effect on the RCS of normalC6normalI6 turned out to be significant, but in normalC6At6 the neglect of the SO coupling is dramatic, quenching the RCS by about 50% .…”
Section: Introductionmentioning
confidence: 99%